Who Can Read Wisdom? The Implied Virtues of the Readers of Wisdom's Narratives. (September 2020) - Briggs, Richard S.
This article contributes to the attempt to reformulate hermeneutical questions about 'how to read the Bible' in terms of theological characterisations of the kind of reader best placed to read the Bible well. It is thus situated amidst renewed interest in the intersection of character ethics and biblical interpretation. It addresses two related issues, before pointing in the direction of a substantive third concern. First, it explores what is at stake in reading wisdom texts as narratives, finding it persuasive to construe wisdom in narrative terms. Secondly, it considers what virtues are presupposed in these narrative constructions. The reading of Job draws us to consider patience; from Proverbs we consider the virtue of perceptiveness; and from Ecclesiastes a virtue of honesty. Thirdly, the larger question of how one might begin to characterise the implied reader of these texts is considered, building on a canonically constructed portrait of the reader informed by the virtues considered.